The spice must flow : the story of Dune, from cult novels to visionary sci-fi movies - Britt, Ryan (Plume, an imprint of Penguin Random House LLC, 2023)
"Geek-culture expert Ryan Britt takes us behind the pages and scenes of the science-fiction phenomenon Dune, charting the series' life from cult sci-fi novels to some of the most visionary movies of all time"--